Conversion of catalogue records from AACR2 to RDA format: what, how and when? (2016)
The paper outlines what it entails to convert catalogue records from AACR2 to RDA format, and how this conversion can be done. An attempt is also made to advice on when the conversion of the records can be done, to make the cataloguing process free of stress. Practical examples are given on how this can be done to achieve success in cataloguing units in all types of libraries.